Baseline survey of marine sediments collected from the State of Kuwait: PAHs, PCBs, brominated flame retardants and metal contamination. Issue 2 (30th November 2015) - Lyons, B.P.; Barber, J.L.; Rumney, H.S.; Bolam, T.P.C.; Bersuder, P.; Law, R.J.; Mason, C.; Smith, A.J.; Morris, S.; Devlin, M.J.; Al-Enezi, M.; Massoud, M.S.; et al.
Abstract: A geographically extensive baseline survey of sediment contamination was undertaken at twenty nine locations around Kuwait. Samples were assessed in relation to a wide range of industrial pollutants, including metals, PAHs, PCBs, PBDEs and HBCDs. The data generated indicated that levels of pollutants were generally low and below commonly applied sediment quality guidelines (SQGs). However, naturally high background concentrations of certain metals present in sediment from the region may prohibit the direct assessment against some of the routinely applied SQGs. Hot spots of contamination were identified for PAHs, PCBs and PBDEs, that were mainly associated with the Shuaiba Industrial Area, located south of the city, and known to contain a diverse mix of both light and heavy industry. Highlights: Hot spots of PAH, PCB and PBDE contamination close to the Shuaiba Industrial Area High background levels of metals may prohibit the use of sediment quality guidelines Contaminant levels in general were low and indicative of clean environments.